Pengaruh Faktor Sosial terhadap Pengelolaan Ternak Sapi Potong di Desa Kampili, Kecamatan Pallangga, Kabupaten Gowa: The Effect of Social Factors on Beef Cattle Management in Kampili Village, Pallangga District, Gowa Regency - Astati; Mursidin; Amriana Hifizah; Anas Qurniawan; Muhammad Basir Paly; A. Mustika Abidin; Fitri Handayani (Universitas Islam Negeri Alauddin Makassar, 2023)
The beef cattle rearing business is one of the businesses that can be used as a source of livelihood for people in rural areas. The benefits of cattle for human life can be classified into economic, nutritional fulfillment and socio-cultural aspects. This study aims to determine the influence of socioeconomic factors on beef cattle management in Kampili Village, Pallangga District, Gowa Regency. This research was conducted in Kampili Village, Pallangga District, Gowa Regency from September to October 2020. This type of research is descriptive quantitative, which is a type of research that explains the influence of socioeconomic factors on the management of beef cattle. Simple random sampling of 42 breeders. The results of multiple linear regression analysis shows that the family environment and community environment affect the management of beef cattle in Kampili Village, Pallangga District, Gowa Regency. Meanwhile, social status has no effect on the management of beef cattle in Kampili Village, Pallangga District, Gowa Regency. Based on this, people in general run beef cattle businesses because of family environmental factors and the community environment not to get higher appreciation from people who do not run this business.